2008
DOI: 10.1007/s00299-008-0565-2
|View full text |Cite
|
Sign up to set email alerts
|

A transient assay to evaluate the expression of polyhydroxybutyrate genes regulated by oil palm mesocarp-specific promoter

Abstract: The promoter of the oil palm metallothionein-like gene (MT3-A) demonstrated mesocarp-specific activity in functional analysis using transient expression assay of reporter gene in bombarded oil palm tissue slices. In order to investigate the tissue-specific expression of polyhydroxybutyrate (PHB) biosynthetic pathway genes, a multi-gene construct carrying PHB genes fused to the oil palm MT3-A promoter was co-transferred with a construct carrying GFP reporter gene using microprojectile bombardment targeting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The specificity of the MSP1 promoter in regulating gene expression in the fruit, especially in the mesocarp would be of great value in metabolic engineering to improve the fruit fatty acid content, as well as to produce high-value novel products from existing intermediates and metabolites (Omidvar et al 2008). Efforts on oil palm genetic engineering thus far have provided nearly all the genes encoding the key enzymes for modification of the fatty acid biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of the MSP1 promoter in regulating gene expression in the fruit, especially in the mesocarp would be of great value in metabolic engineering to improve the fruit fatty acid content, as well as to produce high-value novel products from existing intermediates and metabolites (Omidvar et al 2008). Efforts on oil palm genetic engineering thus far have provided nearly all the genes encoding the key enzymes for modification of the fatty acid biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…EU499363) revealed a strong activity in the mesocarp tissue of oil palm (Siti Nor Akmar and Zubaidah 2007). In a recent study, the fruit-specific activity of the MSP1 promoter was demonstrated using GUS histochemical assay and the promoter was employed to drive the transient fruitspecific expression of the entire polyhydroxybutyrate biosynthetic gene pathway in oil palm (Omidvar et al 2008). Fruit-specific promoters are crucial for improving the nutritional value and quality of fruits by genetic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of site II promoter deletions varied on a day by day basis for a number of promoters tested, and an example of these data, obtained for the RIP promoter, is shown in Supplemental Figure 1A online. This technique has been used extensively to define promoter activity in our laboratory (Thirkettle-Watts et al, 2003;Ho et al, 2008;Giraud et al, 2009) and in other studies (Schmidt et al, 2004;Omidvar et al, 2008), so the variation cannot be ascribed to the method of transformation. The only variation in the above experimental design that we were aware of was the time of transformation during the light cycle.…”
Section: Function Of Site II Elements In Nuclear Genes Encoding Organmentioning
confidence: 99%
“…Similar low levels of PHB were obtained in potato expressing the phb enzymes in the cytosol (Poirier 2002). Transient expression of the three phb biosynthetic proteins has recently been demonstrated in in vitro bombarded slices of oil palm mesocarp tissues, although evidence for polymer production is still lacking (Omidvar et al 2008). The oil palm mesocarp is the site for storage oil synthesis and oil palm is the most productive oil crop in the world.…”
Section: Synthesis Of Polyhydroxybutyrate In the Cytoplasmmentioning
confidence: 59%